Reconstruction to Prove Elements of Detrimental to State Finances in the Criminal Act of Corruption in Indonesia - Firmansyah Firmansyah; Topo Santoso; Febrian Febrian; Nashriana Nashriana (Jurnal Cita Hukum, 2020)
AbstractState financial loss is one of the elements of the criminal act of corruption in Article 2 paragraph (1) and Article 3 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Corruption Crime. The formulation of the element of detrimental to state finances in the two articles at the level of evidence still raises various obstacles because it is an obscure norm and is multi-interpretative. The results of the research show that proving that the element of detrimental to state finances in the criminal act of corruption is still understood as a formal crime so that the proof is sufficient by fulfilling the act and there is no need for consequences, whether potential loss of state finances or actual loss, the perpetrator can be convicted. After the Constitutional Court through its decision Number 25/PUU-XIV/2016 stated that the word "can" in Article 2 paragraph (1) and Article 3 is unconstitutional and has fundamentally changed the qualification of corruption to become a material crime, but in its application there are different views of law enforcement officials in proving that the element is detrimental to state finances, giving rise to legal uncertainty. In the upcoming reform of the criminal law of corruption, a more appropriate model of proof is to use the concept of state financial loss in the sense of the material crime. Through this concept, a new act can be seen as fulfilling the elements of a corruption crime on the condition that there must be an effect that the state loss is real and occurs (actual loss). The concept of proving state financial losses in a material sense ensures fair legal certainty.Keywords: Reconstruction, Evidence, State Financial Losses, Corruption Crime. Abstrak Kerugian keuangan negara merupakan salah satu unsur tindak pidana korupsi dalam Pasal 2 ayat (1) dan Pasal 3 Undang-Undang No. 31 Tahun 1999 Jo Undang-Undang No. 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi. Rumusan unsur merugikan keuangan negara pada kedua pasal tersebut dalam tataran pembuktian masih menimbulkan berbagai hambatan karena merupakan norma kabur dan bersifat multi tafsir. Hasil penelitian menunjukan, meskipun Mahkamah Konstitusi dalam putusannya Nomor 25/PUU-XIV/2016 telah menyatakan kata “dapat” pada kedua pasal tersebut inkonstitusional, telah merubah secara mendasar tindak pidana korupsi menjadi tindak pidana materiel, namun dalam penerapannya terdapat ketidakseragaman pandangan aparat penegak hukum dalam membuktikan unsur tersebut sehingga telah menimbukan ketidakpastian hukum. Model pembuktian yang lebih tepat adalah menggunakan konsep kerugian keuangan negara dalam arti tindak pidana materiel. Melalui konsep ini, suatu perbuatan baru bisa dipandang memenuhi unsur tindak pidana korupsi dengan syarat harus adanya akibat bahwa kerugian negara benar-benar nyata dan terjadi (actual loss). Konsep pembuktian kerugian keuangan negara dalam arti materiel lebih menjamin kepastian hukum yang adil.Kata Kunci: Rekonstruksi, Pembuktian, Kerugian Keuangan Negara, Tindak Pidana Korupsi.АннотацияФинансовые убытки государства являются одним из элементов коррупции в пункте (1) статьи 2 и в статье 3 Закона № 31 от 1999 г. в сочетании с Законом № 20 от 2001 г. Об Искоренении коррупционных преступлений. Расположение элементов, наносящих ущерб государственным финансам, в двух статьях на уровне доказательств по-прежнему создает различные препятствия, поскольку эта норма расплывчата и имеет множество толкований. Результаты исследования показывают, что доказательства элементов, которые наносят ущерб государственным финансам в преступном акте коррупции, по-прежнему понимаются как формальное преступление, так что доказательства являются достаточными путем совершения действия, и нет необходимости в последствиях, будь то потенциальный ущерб государственных финансов или фактических ущерб, виновный может быть осужден.  После того, как Конституционный суд через его решение № 25/PUU-XIV/2016 заявил, что слово «может» в статье 2 (1) и статьи 3 является неконституционным и коренным образом изменил квалификацию коррупции в материальное преступление, но в естественном применении существуют различные точки зрения сотрудников правоохранительных органов в доказательстве того, что эти элементы наносят ущерб государственным финансам , вызывая юридическую неопределенность. В рамках предстоящей реформы уголовного законодательства о коррупции более подходящей моделью доказательства является использование концепции финансовых потерь государства в смысле материального преступления. В рамках этой концепции новый закон может рассматриваться как выполнение элементов преступного коррупционного деяния при условии существования реальных и возникающих потерь государства (фактическая потеря).Ключевые Слова: Реконструкция, Доказательства, Финансовые Потери Государства, Коррупционная Преступность